e-Government Towards Organizational Performance of Malaysia Local Authority: Mediating Effect Information Technology (IT) Capability - Husin, Rohana (Journal of Techno-Social, 2025)
This study proposes electronic government (e-Government) conceptual model to determine the effect of e-Government toward local government performance while investigating the mediating roles of organizational IT capability. By examining the gaps from the prior research, this study intends to answer question about the association among electronic Government, organizational IT capability and organizational performance. The theory of Resources Based View (RBV) is used as a guiding theory to support the proposed conceptual framework. The model was tested using valid and reliable data gathered from a sample of 87 survey forms out of 149 survey forms was passed out to Local Authority in Malaysia. This study uses partial least squares structural equation modelling (PLS-SEM) to test and validate the research model and proposed hypotheses. Finding indicates that the organizational performance is not significantly influenced by e-Government. More importantly, the analysis revealed that IT capability plays a mediating role between variable e-Government and outcome variable organisation performance. It is anticipated that the results of this study will expand the body of knowledge in government studies.